Biofungicidial Activity of Jatropha curcas L. Leaf Extract to Fusarium sp. Growth Inhibition In-vitro - Titalianingtyas, Elva; Ratnasari, Evie (LenteraBio : Berkala Ilmiah Biologi, 2023)
Fusarium sp. is a pathogen that caused wilt disease in agricultural products, especially horticultural crops. Control of Fusarium sp. growth using synthetic fungicides affect the environment, so biofungicides is needed. Jatropha curcas leaf have potential as biofungicide because they contain flavonoids, alkaloids, saponins, tannins, phenols, steroids. The aims of this study was to determine biofungicidal activity of jatropha leaf extract and optimal concentration on inhibiting Fusarium sp. growth. Completely randomized design was used with 7 treatments and 4 repetitions. Concentrations of extract used were 60%, 70%, 80%, 90%, 100%, as well as synthetic fungicide (propineb 70%) positive control and negative control. Diameter of Fusarium sp. colony and percentage of extract inhibition were examined on 7th incubation day. Data were analyzed statistically to determine the differences between treatments. Results showed that there was inhibitory activity of jatropha leaves extract on the growth of Fusarium sp. which were significantly different between treatments. Optimal concentration was 90% with an average growth of 5.08 ± 0.83 cm and an average percentage of inhibition of 43.5 ± 9.11%. From these results it can be concluded that jatropha leaves extract has the potential as a biofungicide in inhibiting the growth of Fusarium sp.